Unraveling the role of 3-mercaptopyruvate sulfurtransferase-derived hydrogen sulfide in triple-negative breast cancer chemoresistance - Hakim, Sousanna; Habashy, Danira A.; Ascenção, Kelly; Youness, Rana A.; Bourquin, Carole; Szabo, Csaba; Gad, Mohamed Z.; Abdelkader, Reham M. (Frontiers in Pharmacology, 2026)
BackgroundTriple-negative breast cancer (TNBC) frequently develops resistance to chemotherapy. Cancer-supporting roles of the endogenous gaseous mediator hydrogen sulfide (H2S) have been identified. We investigated whether endogenous H2S, produced by 3-mercaptopyruvate sulfurtransferase (3-MST), mediates chemoresistance in TNBC and elucidated the underlying mechanisms involved.MethodsA 3-MST inhibitor (HMPSNE) was used along with different chemotherapeutic drugs to determine whether 3-MST affects TNBC cell (MDA-MB-231) chemoresistance. H2S production was measured via AzMC fluorescence. H2S-synthesizing and H2S-degrading enzymes were quantified via Western blotting together with downstream signaling molecules involved in the PI3K/Akt/mTOR pathway. Cell viability, colony formation and migration assays were performed. qRT‒PCR and flow cytometry were conducted to assess the expression of the cancer stem cell marker CD44.ResultsHMPSNE enhanced the cytotoxic, anticlonogenic and antimigratory effects of doxorubicin on MDA-MB-231 cells. Doxorubicin increased H2S-synthesizing enzymes, whereas HMPSNE resulted in their downregulation, especially cystathionine beta-synthase (CBS) and 3-MST. A similar trend was observed for H2S-metabolizing enzymes, particularly thiosulfate sulfurtransferase (TST). A significant increase in CD44 was revealed upon doxorubicin treatment; 3-MST slightly affected this response. With respect to the PI3K/AKT/mTOR pathway, HMPSNE did not significantly modulate the effect of doxorubicin.ConclusionThese findings suggest that TNBC chemoresistance is linked to the 3-MST/H2S pathway. Pharmacological inhibition of 3-MST by HMPSNE enhances the chemotherapeutic effect of doxorubicin on TNBC. Some of these effects may be related to the regulation of CD44 but are unlikely to be mediated via the PI3K/AKT/mTOR pathway. Therefore, pharmacological inhibition of 3-MST may serve as a promising target for further investigations to increase the sensitivity of TNBC cells to doxorubicin-based therapies.